(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2020)
Vocabulary learning is one of the problems in language learning skills. Tackling such problems is to provide useful and effective strategies for enhancing students’ VLSs. Therefore, this study aims to survey vocabulary learning strategies (VLSs) utilized among English as a Foreign Language learners (EFL) in Baghlan University of Afghanistan, and to study the high and least frequently used VLSs that contributes to the learners’ vocabulary knowledge. This study utilizes a descriptive quantitative research method with 67 EFL learners who participated in the survey questionnaire adopted from Oxford (1990) taxonomy of VLS from different faculties of Baghlan University. The findings indicated that EFL learners preferably utilize VLSs at a medium level, and the highly used vocabulary learning strategies are the social strategies through which they ask the native speakers, teachers, and classmates for the meanings of new words in English language conversation. Determination, cognitive, and memory strategies are respectively followed by the learners. Whereas, metacognitive strategies are the least used strategies among EFL learners, the reason is that they only focus on the materials related to examination; explore anything about the new words for learning, and rarely think of their improvement in vocabulary learning.